PENGARUH ALKALISASI KEPING BIJI KAKAO TERHADAP SIFAT FISIK, KIMIA DAN SENSORIS BUBUK KAKAO - , MARITA PURWANDANI ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Alkalization is an addition of alkali into cocoa mass to improve product quality in terms of flavor and colour appearance. A study has been carried out to improve cocoa powder quality that meets the quality standard and market requirement. The research was carried out at the Faculty of Agriculture Engineering, University of Gadjah Mada from October 2013 to March 2014. Cocoa bean was alkalized with variation additions of alkali type of Potassium carbonate and Calcium hydroxide, and also alkali concentration of 0,5%